Haemoparasitic Infections in Cattle from a Trypanosoma brucei Rhodesiense Sleeping Sickness Endemic District of Eastern Uganda - Matovu, Enock; Mugasa, Claire Mack; Waiswa, Peter; Kitibwa, Annah; Boobo, Alex; Mathu Ndung’u, Joseph (Tropical medicine and infectious disease, 2020)
We carried out a baseline survey of cattle in Kaberamaido district, in the context of controlling the domestic animal reservoir of Trypanosoma brucei rhodesiense human African trypanosomiasis (rHAT) towards elimination. Cattle blood was subjected to capillary tube centrifugation followed by measurement of the packed cell volume (PCV) and examination of the bu y coat area for motile trypanosomes. Trypanosomes were detected in 561 (21.4%) out of 2621 cattle screened by microscopy. These 561 in addition to 724 apparently trypanosome negative samples with low PCVs ( 25%) were transported to the laboratory and tested by PCR targeting the trypanosomal Internal Transcribed Spacer (ITS-1) as well as suspect Tick-Borne Diseases (TBDs) including Anaplasmamosis, Babesiosis, and Theileriosis. PCR for Anaplasma sp yielded the highest number of positive animals (45.2%), followed by Trypanosoma sp (44%), Theileria sp (42.4%) and Babesia (26.3%); multiple infections were a common occurrence. Interestingly, 373 (29%) of these cattle with low PCVs were negative by PCR, pointing to other possible causes of aneamia, such as helminthiasis. Among the trypanosome infections classified as T. brucei by ITS-PCR, 5.5% were positive by SRA PCR, and were, therefore, confirmed as T. b. rhodesiense. E orts against HAT should therefore consider packages that address a range of conditions. This may enhance acceptability and participation of livestock keepers in programs to eliminate this important but neglected tropical disease. In addition, we demonstrated that cattle remain an eminent reservoir for T. b. rhodesiense in eastern Uganda, which must be addressed to sustain HAT elimination.
Keywords: Haemoparasites; Human African trypanosomiasis; Elimination; Animal reservoirs